Financial analysis of dipterocarp log production and rubber production in the forest and land rehabilitation program of Sekolaq Muliaq, West Kutai District, Indonesia - ABUBAKAR M. LAHJIE; B.D.A.S. SIMARANGKIR; R. KRISTININGRUM; YOSEP RUSLIM; AGUS LEPONG (Biodiversitas Journal of Biological Diversity, 2018)
Lahjie AM, Lepong A, Simarangkir BDAS, Kristiningrum R, Ruslim Y. 2018. Financial analysis of dipterocarp log production and rubber production in the forest and land rehabilitation program of Sekolaq Muliaq, West Kutai District, Indonesia. Biodiversitas 19: 757-766. The Dayak community of East Kalimantan in the last decade has begun to develop production systems that integrate forest timber tree species into plantation commodity enterprises. They have become aware that the natural forest species of their surroundings such as Meranti (Shorea sp.) and Kapur (Dryobalanops aromatica) are often easier to exploit economically, and represent potentially cheaper investments, than are introduced plantation crops such as rubber (Hevea brasiliensis). This is because the price of rubber latex has decreased over the years and has ceased to give a financial return commensurate with the investment required to develop rubber as a monocrop. The research described in this paper aimed to evaluate the viability of a dipterocarp forest/rubber plantation system cultivated by people in the West Kutai District of East Kalimantan. The viability of the system was evaluated by (i) measuring its production of dipterocarp logs and natural rubber; (ii) determining the diameter distribution of its dipterocarp trees and (iii) assessing the financial feasibility of the dipterocarp/rubber system using the theories of increment production and basal area applied to the determination of Pay Back Period, Net Present Value (NPV), Net Benefit Cost (B/C) ratio and Internal Rate of Return (IRR). The research areas on which the evaluation was performed consisted of (1) a mixed population of Shorea spp. (Meranti) and rubber (Hevea brasiliensis) and (2) a mixed population of Dryobalanops aromatica (Kapur) and rubber. The growth analysis of Shorea spp. combined with rubber as well as D. aromatica combined with rubber at the planting distance of 5m x 5m showed that the maximum cycle was reached at the age of 40 years. Whereas the rubber trees in monoculture cultivation reached their maximum cycle at the age of 17 years. The optimum increment of MAI and CAI of Shorea spp. combined with rubber reached 3.61 m3 ha-1 year-1 and 3.62 m3 ha-1 year-1 respectively. The maximum increment of MAI and CAI of Dryobalanops aromatica combined with rubber reached 3.09 m3 ha-1 year-1 and 3 m3 ha-1 year-1 respectively.